Affective social anthropomorphic intelligent system - Mamun, Md. Adyelullahil; Abdullah, Hasnat Md. (Brac University, 2021)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2021.